Postpartum bloody nipple discharge-rusty pipe syndrome: A case report - Prasad, Ananya S; Ananthen, Neena (Indian Journal of Case Reports, 2025)
In the early postpartum period, a primiparous woman who shows unilateral bloody nipple discharge ought to likely be evaluated for rusty pipe syndrome (RPS). It is rare and can be brought on by a physiological condition that mostly affects primiparous women who have enhanced ductal and alveolar vascularization as a result of lactation. Here, we report the case of a 34-year-old primigravida who presented with unilateral painless and bloody nipple discharge after delivery. Her breast examination showed no signs of infection or structural changes, and the breast ultrasound did not reveal any significant compliances. Five days after the onset of lactation, the bloody nipple discharge stopped and lactation continued on demand. Since traditional textbooks do not cover RPS, we felt that it would be appropriate to alert readers to this benign condition and to avoid unnecessary investigations.